Matfre Ermengaud, lecteur, maître et juge des troubadours - Valérie Fasseur (Revue des Langues Romanes)
The treatment of the troubadour quotations contained in the Perilhos tractat, which forms the third branch of Matfre Ermengaud’s Breviari d’Amor, is a clever construction of authority, transferred from the former troubadours to the author of the Breviari. By modelling a doctrinal discourse based on a debate on fin’amor, this one makes each troubadour cited the emblem of a moral posture, which explains the representation conferred on each person by textual posterity and justifies the place that Matfre gives him in the afterlife.